Comprehensive study on impact of hydrogen peroxide decomposition on the crucial parameters of OSM-type energetic materials - Mateusz Polis; Agnieszka Stolarczyk; Konrad Szydło; Magdalena Fabin; Mateusz Pytlik; Barbara Lisiecka; Tomasz Jarosz (Scientific Reports)
Abstract The use of increasingly advanced energetic materials (EMs) in various branches of industry and military sectors increases the appropriate requirements for EMs, including: their durability, safety of use, chemical and high-energetic properties. Additionally, the impact of the products of the explosion of EMs on the natural environment is also crucial. Therefore, on-site mixture (OSM) energetic materials containing concentrated hydrogen peroxide (OSM-type energetic materials) are becoming increasingly popular. This is an extremely interesting group of materials that contains in excess of 50 wt.% hydrogen peroxide (HP) and not containing toxic compounds, and therefore is environmentally friendly. The main objective of the study was to investigate the various compositions of OSM-type energetic materials in terms of the evolution over time of their energetic properties (including the “raw” energetic material strength and the ability to sustain the propagation of a detonation wave) and the volume of the post-detonation gases. The obtained results show that the decomposition of hydrogen peroxide strongly affects the detonation parameters of OSM-type energetic material and the decomposition time of HP. In addition, it has been proven that rate of decomposition of HP significantly affects the detonation parameters of OSM-type energetic materials. It was also found that the concentration of NO $$_{\hbox {x}}$$ x is low and decreases dramatically with the decomposition of hydrogen peroxide, but at the same time the concentration of carbon oxides increases.